The Savvy Survey #6d: Constructing Indices for a Questionnaire - Anil Kumar Chaudhary; Glenn D. Israel (EDIS, 2016)
One of the Savvy Survey Series, this article will help Extension agents understand indexes and how to use them when evaluating an educational program. This 6-page fact sheet provides an overview of constructing indices for a questionnaire. Specifically, it will discuss why composite measures like index numbers are important, what the index number means, the difference between indexes and scales, steps for the construction of indexes, and recommendations for use by Extension educators. Written by Anil Kumar Chaudhary and Glenn D. Israel, and published by the Agricultural Education and Communication Department, December 2015.